2021
DOI: 10.3389/fcell.2021.684505
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Fibroblast-Derived Interleukin-8 Promotes Ovarian Cancer Cell Stemness and Malignancy Through the Notch3-Mediated Signaling

Abstract: As a significant component in ovarian cancer microenvironment, cancer-associated fibroblasts (CAFs) contribute to cancer progression through interaction with cancer cells. Recent studies demonstrate that interleukin-8 (IL-8) is overexpressed in multiple cancer types and is essential for tumor development. Nonetheless, the underlying mechanism that the CAF-derived IL-8 promotes ovarian tumorigenesis is unknown. Here, we show that IL-8 secreted from CAFs could activate normal ovarian fibroblasts (NFs) through mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 39 publications
7
55
0
Order By: Relevance
“…Zhou et al reported that exosomes released from TAMs transfer miRNAs that induce a Treg/Th17 imbalance and generate an immune-suppressive microenvironment that facilitates OC progression and metastasis [ 55 ]. Ji et al showed that IL-8 secreted from CAFs could stimulate malignant growth and increased OC cisplatin resistance [ 56 ]. The above suppressive cells can cause dysfunction in effector T cells, causing a state called “T cell exhaustion.” It is characterized by progressive loss of function, changes in transcriptional profiles, and sustained expression of inhibitory receptors [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al reported that exosomes released from TAMs transfer miRNAs that induce a Treg/Th17 imbalance and generate an immune-suppressive microenvironment that facilitates OC progression and metastasis [ 55 ]. Ji et al showed that IL-8 secreted from CAFs could stimulate malignant growth and increased OC cisplatin resistance [ 56 ]. The above suppressive cells can cause dysfunction in effector T cells, causing a state called “T cell exhaustion.” It is characterized by progressive loss of function, changes in transcriptional profiles, and sustained expression of inhibitory receptors [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-8 is another molecule that plays a critical role in tumor progression and metastasis in different cancers. In ovarian cancers, CAF-derived IL-8 promotes normal fibroblast proliferation and stemness of tumor cells, activating the Notch-3 signaling pathway [ 99 ]. In addition, in pancreatic cancer, a subtype of CAFs with senescent features secretes more IL-8 than non-senescent CAFs.…”
Section: Caf–tumor Communicationmentioning
confidence: 99%
“…CXCL8 can induce normal ovarian fibroblasts to CAFs and stimulate xenograft tumor growth in mice. The ovarian cancer cell stemness was promoted by the CXCL8 secreted from CAFs through the Notch3 signaling pathway [ 50 ]. Gastric cancer extracellular vesicles transfer various miRNAs and induce chemokines such as CXCL1 and CXCL8 expression in CAFs.…”
Section: Cxcl8-cxcr1/2 Signaling Pathwaymentioning
confidence: 99%